2012
DOI: 10.1590/s0004-282x2012000100008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of EEG in the diagnosis and management of patients with acute impairment of consciousness

Abstract: With the advent of neuroimaging techniques, such as high resolution MRI, PET and SPECT, the importance of the electroencephalogram (EEG) in cerebral disease studies had decreased. However, nowadays, it has received high attention as an important source of information, especially in situations such as unexplained impairment of consciousness [1][2][3] , since it may offer valuable real time information about brain activity, which can be decisive in some life-threatening situations, as convulsive status epileptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…A grande maioria dos estudos encontrados na literatura acerca do EEG os descrevem associados a uma patologia específica (BORGES et al, 2004;KING et al, 1998;MARINO JÚNIOR;CUKIERT;PINHO, 1986) Quanto ao gênero, o estudo em voga apresentou uma proporção de homens para mulheres de 0,81% que se assemelha às taxas já descritas por outros trabalhos. (BORGES et al, 2004;OLEJNICZAK, 2006;RICARDO et al, 2012;SENEVIRATNE et al, 2013) Entretanto, é de se esperar que em estudos que tratem do EEG em uma doença específica, as taxas de frequência de sexo e idade obedeça a epidemiologia associada a esta. Grande parte dos EEGs analisados foram solicitados para investigação de cefaleia e este distúrbio é classicamente descrito como mais comum no sexo feminino, o que corrobora com o maior número de solicitações neste sexo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A grande maioria dos estudos encontrados na literatura acerca do EEG os descrevem associados a uma patologia específica (BORGES et al, 2004;KING et al, 1998;MARINO JÚNIOR;CUKIERT;PINHO, 1986) Quanto ao gênero, o estudo em voga apresentou uma proporção de homens para mulheres de 0,81% que se assemelha às taxas já descritas por outros trabalhos. (BORGES et al, 2004;OLEJNICZAK, 2006;RICARDO et al, 2012;SENEVIRATNE et al, 2013) Entretanto, é de se esperar que em estudos que tratem do EEG em uma doença específica, as taxas de frequência de sexo e idade obedeça a epidemiologia associada a esta. Grande parte dos EEGs analisados foram solicitados para investigação de cefaleia e este distúrbio é classicamente descrito como mais comum no sexo feminino, o que corrobora com o maior número de solicitações neste sexo.…”
Section: Discussionunclassified
“…Por fim, contribui-se com a literatura ao demonstrar aquilo que é classicamente descrito, de que alterações em termos de modulação, simetria e sincronia não necessariamente prediz padrões patológicos nos EEG. (OLEJNICZAK, 2006;PRALINE et al, 2007;RICARDO et al, 2012) Haja vista que foram encontradas ondas mal moduladas, assimétricas e assincrônicas em exames sem nenhum grau de disfunção.…”
Section: Discussionunclassified
“…Critically ill patients with unexplained alteration of mental status in ICU and ED might also suffer this condition. Epileptic activity was recently found in the EEG of almost half of patients with acute impairment of consciousness, 18 and it has been demonstrated that delayed diagnosis and treatment of NCSE may lead to increased neurological complications and mortality 16 19 There is currently no standardized protocol for identifying the patients with suspected NCSE, and no after-hours urgent EEG availability even in some tertiary care centers 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, EEGs confirmed diagnosis and altered management in 0-22% of the patients [4,11,14]. Higher yield of abnormal findings and higher rates of contribution to making the diagnosis (42-100%) were reported in the emergent setting, when EEGs were performed for diagnosis of nonconvulsive and subtle status epilepticus, follow-up of convulsive status epilepticus and suspected cerebral death in patients presented to the emergency department or admitted in intensive care units with altered mental states, although low rates of 5% and 10Á7% of status epilepticus confirmation were reported in these patients as well [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%